Renormalization of the valence and conduction bands of (C6H5C2H4NH3)2PbI4 hybrid perovskite. (30th June 2021) - Lee, Min-I; Khan, Saleem Ayaz; Mrezguia, Hela; Barragán, Ana; Nair, Maya N.; Khelidj, Hamza; Ksari, Younal; Giovanelli, Luca; Themlin, Jean-Marc; Lédée, Ferdinand; Trippé-Allard, Gaëlle; Deleporte, Emmanuelle; et al.
Abstract: Quasi two-dimensional hybrid organic-inorganic perovskites (HOIPs) have been rediscovered recently for photovoltaics due to a higher stability than other HOIPs. We focus here on the electronic structure of the 2D perovskite (C6 H5 C2 H4 NH3 )2 PbI4 . We perform an experimental k-resolved determination of the valence and conduction bands by angle-resolved photoemission spectroscopy (ARPES) and inverse photoemission spectroscopy (IPES). The experimental and theoretical dispersions are compared. The valence band width is in agreement with that of renormalized theoretical bands, while no significative renormalization is observed for the conduction band. The effect of the spin–orbit coupling in the conduction band is also experimentally observed.